Prevalence of Lentilacobacillus hilgardii over Lactiplantibacillus plantarum in Low-Temperature Spontaneous Malolactic Fermentation of a Patagonian Pinot Noir - Manera, Camila (2023)
The spontaneous malolactic fermentation (MLF) in a centenary winery from Patagonia, Argentina, is conducted by predominantly mesophilic Oenococcus oeni and Lactiplantibacillus plantarum. In this region, MLF takes place from 14 to 4 °C, leading to heat cellars incurring in higher costs and non-sustainable practices. Previously, psychrotrophic strains of O. oeni had been obtained from a Patagonian wine. The goal of this work was to identify the Lactobacillaceae microbiota related to low-temperature MLF and assess their contribution. Nine sychrotrophicc Lentilactibacillus hilgardii strains were identified by sequencing the 16S rRNA gene, and the strains typified by RAPD-PCR. All strains consumed L-malic acid at 4 and 10 °C in sterile wine. The selected UNQLh1.1 strain revealed implantation capacity and L-malic acid consumption at 4 and 10 °C in the presence of the native microbial consortium. Furthermore, the histidine decarboxylase (hdc) gene was not detected in any of the Len. hilgardii strains. The prevalence of Len. hilgardii under low-temperature conditions represents a novelty compared to previous findings of LAB diversity in the MLF of Patagonian wines. The native Patagonian psychrotrophic Len. hilgardii strains are a new player in fermentations conducted at low temperatures with the potential to be used as a sustainable MLF starter.